2022
DOI: 10.2147/ijgm.s380208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Key Genes for Slow Transit Constipation Based on RNA Sequencing

Abstract: This study aims to identify key genes in slow transit constipation (STC). We also sought to explore the potential link between STC and colorectal cancer. Patients and Methods: mRNA expression profiles were obtained by RNA sequencing, and differentially expressed genes were identified. Functional enrichment analysis and a protein-protein interaction (PPI) network was explored, and differentially expressed genes common to STC and colorectal cancer were examined. Analysis of the effect of constipation and colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been confirmed that the increase of AQP3 leads to spasm of intestinal smooth muscle, thus enhancing intestinal water absorption, reducing intestinal peristalsis frequency and causing constipation. 17 Aquaporin 4 is also one of the common AQPs that cause STC. This kind of AQPs is present in the absorption epithelial cells, mainly participates in the intestinal absorption and has a certain regulatory effect on constipation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the increase of AQP3 leads to spasm of intestinal smooth muscle, thus enhancing intestinal water absorption, reducing intestinal peristalsis frequency and causing constipation. 17 Aquaporin 4 is also one of the common AQPs that cause STC. This kind of AQPs is present in the absorption epithelial cells, mainly participates in the intestinal absorption and has a certain regulatory effect on constipation.…”
Section: Discussionmentioning
confidence: 99%